Suture-Bridge Fixation of Osteochondrial Fractures and Osteochonritis Dissecans in the Adolescent Knee: Mir Assement of Healing. Issue 5 (31st May 2022) - Ellis, Henry B.; Wyatt, Charles W.; Johnson, Benjamin L.; Carpenter, Connor M.; Wilson, Philip L.
Background: Preservation of articular cartilage in the setting of adolescent knee injury is paramount for long-term joint health. Achieving osseous union, minimizing implant related injury, and eliminating need for reoperation for osteochondral fracture lesions (OCL) and osteochondritis dissecans (OCD) remain a challenge for orthopedic surgeons. Hypothesis/Purpose: To evaluate MRI appearance of osseous and chondral integration following suture bridge construct. Secondarily, to assess short-term complications and outcomes of suture bridge fixation of OCL and OCD in adolescent knees. Methods: Consecutive patients (n=41) treated within a pediatric sports medicine institution who underwent suture-bridge knee fixation of an OCL or OCD from 10/2019-03/2021 were reviewed. MRI within 6 months of surgery was required. Analysis included demographics, pre-operative MRI lesion characteristics, surgical technique, suture type, Postoperative MRIs for lesion healing (Full Union: 100% cancellous/cancellous-chondral lesion continuity, Stable Union: >50% continuity with some fibrous tissue present, Un-united: < 50% continuity and extensive fibrous signal or fluid below the lesion), complications, rates and timing of return-to-sport (RTS), and short-term patient-reported outcomes (Pedi-IKDC, Pedi-FABS, KOOS Symptoms, PROMIS® ). Results: 22 knees (20 patients) included 11 OCL and 10 OCD (Table 1). Lesion characteristics: OCL-mean size=248.2(140-459)mm 2, mean major length=17.3(12-27)mm, osteochondral= 10(83%), all chondral= 2(17%); OCD-mean size =374.4(130-780)mm 2, mean major length=19.3(10-29)mm, progeny bone present =7(70%). 91%(20/22) were treated via mini-arthrotomy, and 86%(19/22) of constructs were absorbable suture. At MRI follow up (6.7 months, 3.0-21.1), OCLs demonstrated 91.7% Full Union, 8.3% Stable Union, 0% Un-united; OCDs demonstrated 50% Full Union, 50% Stable Union, 0% Un-united. At average of 6.4 months, 19(86%) knees had RTS. Pedi-FABS demonstrated a return to similar level of activity and Pedi-IKDC indicated functional improvement in 80% on average 9.6 months post-operatively (Table 2). There were 2 (9.1%) complications (1. repeat arthroscopy for chondroplasty and marrow stimulation for 20% distal margin instability of patellar OCL secondary to patellar instability, 2. Second surgery for patellar stabilization following trochlear OCD suture-bridge in the setting of trochlear dysplasia and no stabilization at primary procedure) and no re-operations needed for suture-bridge construct. Conclusion: In this series of knee OCLs and OCDs, suture-bridge fixation demonstrates excellent rates of healing based on MRI appearance and good early outcomes with minimal short-term complications. This technique may be used by surgeons to avoid loose body removal and marrow-stimulation, and have significant benefits in comparison to metallic and non-metallic screw/tack constructs in the treatment of these challenging lesions. Longer term follow-up and investigation is warranted. Table 1. Patient Demographics and Lesion Location Table 2. Patient Reported Outcomes